Morfometría de Sanguinolaria cruenta (Bivalvia: Psammobidae) en playa Tucacas, Falcón, Venezuela - Martín, Alberto; Díaz Díaz, Yusbelly J; Paredes, Claudio (Revista de Biología Tropical, 2001)
Three hundred and twelve shells of Sanguinolaria cruenta were collected in May 1999 in a sandy beach in Tucacas, Falcón, Venezuela. For each shell, antero-posterior length (Lap), overall height (Al), wide (An), weight (Pe), valves area (Arv), anterior length (La) and dorsal height (Ad) were measured. The descriptive statistic of the studied individuals, allows to appreciate that the variables that are good as parameters for the taxonomic description of S. cruenta are: Lap, Al, An, La y Ad, given their little variability. The maximum class frequencies is 41-70 mm for Lap (91 % of the population). Analysis of data determined relationships of Lap to An, Lap to La were isometric (Lap = 0.98078 An + 1.50456 and Lap = 0.98052 La + 5.25840, respectively), whereas the other relationships indicate allometric growth.